Analysis Of Mitigation Strategy For Operational Supply Risk: An Empirical Study Of Halal Food Manufacturers In Malaysia - Musa, Haslinda; Azmi, Fadhlur Rahim; Fam, Soo Fen; Mohamad Zailani, Suhaiza Hanim (Growing Science, 2021)
This study aims empirically to analyze mitigation strategies for operational supply risk among halal food manufacturers in Malaysia. A survey of 369 halal food manufacturers is used to test a research model that proposes a relationship between operational supply risk and risk consequences as well as the mediating role of risk mitigation strategies. Structural equation modeling reveals that in the absence of a risk mitigation strategy (behavior-based management, buffer-based management, and traceability-based management), operational risk consequences are significantly influenced by operational supply risk. The analysis also showed the mitigation strategies reduce risk events by its interaction between operational supply risk and risk consequences. This study shows significant data about the management of halal food manufacturing. Due to the limitations of this survey, further study is necessary to analyze how other halal's sectors manage their supply chain risk management.